Willingness to pay for social health insurance among informal sector workers in Wuhan, China: a contingent valuation study - Bärnighausen, Till; Liu, Yuanli; Sauerborn, Rainer (BMC health services research, 2007)
Most of the about 140 million informal sector workers in urban China do not have health insurance. A 1998 central government policy leaves it to the discretion of municipal governments to offer informal sector workers in cities voluntary participation in a social health insurance for formal sector workers, the so-called 'basic health insurance' (BHI).
Gesehen am 27.06.2017